CUL4B-DDB1-COP1-mediated UTX downregulation promotes colorectal cancer progression - Luo, Dakui; Chen, Min; Li, Qingguo; Wang, Kangjunjie; Wang, Kaihua; Li, Junqiang; Fu, Guoxiang; Shan, Zezhi; Liu, Qi; Yang, Yufei; Liang, Lei; Ma, Yanlei; et al. (Experimental hematology & oncology, 2023)
Background UTX (encoded by KDM6A), a histone demethylase for H3K27me2/3, is frequently mutated in human cancers. However, its functional and regulatory mechanisms in colorectal cancer (CRC) remain unclear. Methods Immunohistochemistry staining was used to investigate the clinical relevance of UTX in CRC. Additionally, we generated a spontaneous mouse CRC model with conditional Utx knockout to explore the role of UTX in the colorectal tumorigenesis. Post-translational regulation of UTX was determined by co-immunoprecipitation and immunoblot analyses. Results Herein, we identify that downregulation of UTX, mediated by the Cullin 4B-DNA Damage Binding Protein-1-Constitutive Photomorphogenesis Protein 1 (CUL4B-DDB1-COP1) complex, promotes CRC progression. Utx deletion in intestinal epithelial cells enhanced the susceptibility to tumorigenesis in AOM/DSS-induced spontaneous mouse CRC model. However, this effect is primarily alleviated by GSK126, an inhibitor of histone methyltransferase EZH2. Mechanistically, EMP1 and AUTS2 are identified as putative UTX target genes mediating UTX functions in limiting intestinal tumorigenesis. Notably, the CUL4B-DDB1-COP1 complex is identified as the functional E3 ligase responsible for targeting UTX for degradation in CRC cells. Thus, Cop1 deficiency in mouse intestinal tissue results in UTX accumulation and restricts tumorigenesis. Furthermore, patient cohort analysis reveals that UTX expression is negatively correlated with clinical stage, favorable disease outcomes, and COP1 expression. Conclusions In the current study, the tumor suppressor function and regulation of UTX in CRC provide a molecular basis and the rationale to target EZH2 in UTX-deficient CRC. Keywords: Colorectal cancer, COP1, Ubiquitylation, UTX